High School Achievement in Maine: Where You Come From Matters More Than School Size and Expenditures - Desjardins, Fern; Donaldson, Gordon (Maine Policy Review, 2008)
Fern Desjardins and Gordon Donaldson report on their research examining the relationship between academic achievement in Maine’s public high schools and school size, per-pupil operating costs, and socioeconomic status. Using aggregated Maine Educational Assessment (MEA) scores, their study confirmed previous research that socioeconomic status (using both family and community measures) is the most important factor associated with achievement, while school size is not a critical factor. Additionally, the authors found that per-pupil operating costs are higher in the state’s largest and smallest high schools. The authors suggest that the creation of larger districts and larger schools, as supported by recent state policies, will not necessarily mitigate inequities in student achievement resulting from family and community socioeconomic status, and may not yield the desired cost savings.
Keywords: Maine; high school education; socioeconomic status and academic acheievement; school size and academic achievement